Black student intellectuals and the complexity of entailment in the #RhodesMustFall movement - Naidoo, Leigh-Ann (My University, 2020)
The University of Cape Town (UCT), a colonial university established for the education of elite white liberals during the colonial and apartheid periods in South Africa, became subject to increasing anti-racist critique as it hosted growing numbers of black students and staff after the end of apartheid. This anti-racist dissent slowly accrued and broke in 2015 with the #RhodesMustFall (RMF) student movement. The protest was initially directed towards the statue of Cecil John Rhodes at the centre of the university’s main campus but quickly became an important space for a broad critique of South African society and the university’s place within it. This thesis tracks the emergence and the sustained work of the students in the movement over the course of 2015, paying particular attention to the ways in which a cadre of powerful student intellectuals was built in and through the movement. Compelled by the movement’s ideas and its confidence to disrupt post-apartheid’s impotent nonracial consensus, the research took shape in solidarity with the movement and at the heart of the movements planning, coordination and conversation. Through a detailed account of the movement’s occupations of university buildings, its Subcommittee work (in particular its Education Subcommittee) and the creative disruptions of campus space, the thesis makes the argument that fierce intellectual activity was elicited because of the collective anti-hegemonic entailment of black students in the disruption of the white university. Anti-hegemonic entailment is read as grounded radical praxis that critiques and shifts the normative ground of oppression and privilege. The emphasis on entailment is to recognise the complicity that is created at the level of subjective experience in reinforcing oppressive practices and structures. The capacity to refuse hegemonic entailment in systems of oppression, especially as a generational cohort, requires immense intellectual work and collective action. The thesis uses several concepts from the literature on intellectuals to understand the work of the student movement. Most importantly Wallerstein’s notion of the “honest intellectual”, Said’s idea of the intellectual as oppositional and exiled, and a range of writers from the black radical tradition to argue that making explicit the political, moral and historical stakes of the white university allowed students in RMF to take over the intellectual project of the university. During 2015, black students became the new educators of a dishonest university institution, in so doing creating themselves as the more compelling intellectuals of the moment. The negotiated settlement that ended formal apartheid focused on the priority of racial desegregation, which opened historically white institutions of all kinds to black people. In education, this strategy included black students in white schools and universities, staging black proximity to white institutions without any reworking of their institutional culture. This thesis traces how black students began to reflect on their experiences of racism and other forms of oppression and marginalisation at the university as an experience of painful alienation and assimilation, an experience they described as “black pain”. These alienating experiences fuelled anti-assimilationist impulses and they began the collective intellectual and activist work of painstakingly revealing the hidden curriculum of colonial education and white subjectivity at the heart of the project of UCT.RMF took over the pedagogical space of UCT during the time of the movement. It also took on the responsibility for changing the nature of the institution, refusing the liberal form and politics of “transformation”, and asserting in its place a radical form and politics of decolonisation. The thesis makes careful account of the critical collective conversations and actions that the movement hosted, theorising that its critical confrontations across different politics and subjectivities within the condition of black struggle created a rich democratic and anti-hierarchical praxis. One of the most important expressions of this praxis was the experimental relationship established between plenary and caucus. RMF, along with other black-led student formations at historically white universities, gave shape to the decolonisation agenda at South African universities and beyond, and informed many of the ideas of the more mass-based anti-privatisation-focused national student movement that emerged in October 2015 under the name #FeesMustFall (FMF)
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020